Simple GUI design for monitoring of a remotely operated quadrotor unmanned aerial vehicle (UAV) - Zul Azfar, Ahmam; Hazry, Desa, Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/